Ergonomic embedded in designing welding assembly tool for automotive manufacturing process - M. F., Hamizatun; S. A, Haikal; Nik Mohd Zuki, Nik Mohamed (Penerbit UMP, 2023)
Ergonomics focuses on understanding how workers interact with their work environment, tools, and equipment. The proper ergonomics consideration in tool design will impact worker safety and productivity. Ergonomics-embedded knowledge is critical in designing welding assembly tools for automotive manufacturing. The study aims to improve the ergonomic issues faced by the automotive assembly welders. The methodology involves studying the existing welding assembly process in automotive manufacturing regarding RULA scores and simulating the postures using CATIA analysis. Based on the simulation, critical ergonomics issues should be identified and analyzed. Finally, the welding process is improved by designing the hand support for the workers to assemble parts. The results revealed that the RULA scores have improved from 7 (high risk at the existing condition) to 3 (medium risk) for both worker's hands after the support of the assembly tool. In conclusion, ergonomic embedding in welding assembly tool design has improved the automotive assembly worker's well-being. The findings of this study contribute to the growing body of knowledge on integrating ergonomics into automotive manufacturing processes, providing valuable insights for industry practitioners and researchers alike.